Q&A: ICTs, agrometeorology and farmers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Making agricultural meteorology more operational is not enough to help farmers. According to Professor Kees Stigter, the knowledge gap is very real and only strong policies can overcome it.